Alt-i-alt: Et gensyn med Poul Borums syn på Digteren Grundtvig - Hauge, Hans (Grundtvig-Studier, 2009)
Alt-i-alt: Et gensyn med Poul Borums syn på Digteren Grundtvig [All in all: Poul Borum''s view of Grundtvig the poet revisited] By Hans Hauge Poul Borum was a well-known poet and an influential critic. His book on poetic modernism was a milestone. Few contemporaries associated him with N. F. S. Grundtvig so it was perhaps something of a surprise when in 1983 he published a full-length study of Grundtvig’s texts, focusing upon and rehabilitating Grundtvig the poet. He was of the opinion that literary critics and writers at large as well as established Grundtvig-scholars lacked something. The literary critics knew too little about Grundtvig and did not adequately appreciate him, whereas the scholars were too unfamiliar with contemporary literary criticism. Borum attempted to mediate between the two groups. He was easily familiar with almost all the secondary and scholarly literature on Grundtvig and he was also well versed in contemporary literary criticism and referred to such names as Harold Bloom and Paul de Man. He uses Bloom’s theory of anxiety in his reading of one of Grundtvig’s best-loved hymns and demonstrates how Grundtvig struggled with the influence of the seventeenthcentury hymn-writer Kingo. Borum did not really succeed in achieving deconstructive readings of Grundtvig’s texts; however, he did successfully demonstrate the way in which all Grundtvig’s texts were self-reflexive and he showed how even brief fragments contained the whole - all in all. Whenever Grundtvig wrote something, the text contained poetological elements and he stressed the notion of contemporaneity. The article concludes by discussing how Borum took various critics to task and how he distanced himself from certain contemporary political uses of Grundtvig.